3D lattice Boltzmann simulation of droplet evaporation on patterned surfaces: Study of pinning–depinning mechanism. (April 2020) - Dong, Boheng; Wang, Fuxian; Zhang, Xinya; Jiang, Xiang
Highlights: The local force balance theory reveals Pinning–depinning mechanism of the 3D droplet. We propose an equation to accurately predict the contact angle of the 3D droplet. When the local force balance is broken, it will cause asymmetric migration. Abstract: The liquid–vapor phase change lattice Boltzmann method is used to investigate the pinning–depinning mechanism of the contact line during droplet evaporation on the stripe-patterned surfaces in 3D space. Considering the curvature of the contact line and the direction of the unbalanced Young's force, the local force balance theory near the stripe boundary is proposed to explain the steady state of the droplets on the stripe-patterned surfaces. An equation is proposed to evaluate the characteristic contact angle of the stabilized droplets. During the evaporation of the droplet, the stick-slip-jump behavior and the CCR-Mixed-CCA mode can be well captured by the lattice Boltzmann simulation. When the contact line is pinned to the stripe boundary, the contact line in the direction perpendicular to the stripes is slowly moving while the curvature of the contact line is gradually increasing. The gradually increasing curvature of the contact line accelerates the movement of the contact line, and the final contact line is detached from the stripe boundary. The research results provide theoretical support and guidance for the design, improvement and application of patterned surfaces in the field of micro-fluidic and evaporation heat transfer. Graphical abstract: Image, graphical abstract